2016
DOI: 10.1111/raq.12145
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and vitrification of fish semen: a review with special emphasis on marine species

Abstract: Semen conservation methods have been extensively studied for fish species over the last 60 years. Cryopreservation techniques can be divided into two types: one with slow cooling rates like traditional freezing and the other with ultrarapid rates as used in vitrification. These protocols increase the time over which semen samples can be used for reproduction or sperm quality analysis. Marine fish possess greater resistance than freshwater species to variations in osmolality. This favours the application of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 84 publications
3
55
1
4
Order By: Relevance
“…One of the ways to do so is through germplasm cryopreservation. Perhaps not surprisingly, aside from research in humans, studies on germplasm cryopreservation have largely focused on advances in technology for livestock (e.g., Morrell & Mayer, 2017;Sieme & Oldenhof, 2015;Singh, Mal, & Singla, 2017) and aquaculture management (e.g., reviews by Asturiano, Cabrita, & Horváth, 2017;Martinez-Paramo et al, 2017;Magnotti et al, 2018). Perhaps not surprisingly, aside from research in humans, studies on germplasm cryopreservation have largely focused on advances in technology for livestock (e.g., Morrell & Mayer, 2017;Sieme & Oldenhof, 2015;Singh, Mal, & Singla, 2017) and aquaculture management (e.g., reviews by Asturiano, Cabrita, & Horváth, 2017;Martinez-Paramo et al, 2017;Magnotti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to do so is through germplasm cryopreservation. Perhaps not surprisingly, aside from research in humans, studies on germplasm cryopreservation have largely focused on advances in technology for livestock (e.g., Morrell & Mayer, 2017;Sieme & Oldenhof, 2015;Singh, Mal, & Singla, 2017) and aquaculture management (e.g., reviews by Asturiano, Cabrita, & Horváth, 2017;Martinez-Paramo et al, 2017;Magnotti et al, 2018). Perhaps not surprisingly, aside from research in humans, studies on germplasm cryopreservation have largely focused on advances in technology for livestock (e.g., Morrell & Mayer, 2017;Sieme & Oldenhof, 2015;Singh, Mal, & Singla, 2017) and aquaculture management (e.g., reviews by Asturiano, Cabrita, & Horváth, 2017;Martinez-Paramo et al, 2017;Magnotti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…; Magnotti et al . ). It is also possible, in some cases, that DNA defects in the sperm may be repaired by the oocyte repair system after fertilization, as in the case of Logurnus fossilis (Kopeika et al .…”
Section: Embryo Survival and Qualitymentioning
confidence: 97%
“…; Magnotti et al . ). On the other hand, several works have demonstrated that sperm cryopreservation generates damage to DNA in mammals (Hu et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, due to its simplicity, speed, and utility for field applications with no equipment required, it offers a new approach to preserve genetic resources and to reconstitute strains or lines (Moore and Bonilla 2006; Saragusty and Arav 2011; Magnotti et al, in press). Vitrification is best suited for use in three areas: biomedical research fish models, genetically improved lines, and imperiled species.…”
mentioning
confidence: 99%
“…Most recently, sperm motility and sperm head morphometry were evaluated after vitrification of the marine European Eel Anguilla anguilla (Kasa et al, in press). However, these studies did not attempt fertilization or offspring production (Magnotti et al, in press). …”
mentioning
confidence: 99%